Assessment Instrument Development for a Chronological Thinking Skills with the Rasch Model - Ofianto Ofianto; Tri Zahra Ningsih (STAI Hubbulwathan Duri, 2021)
Chronological thinking skills are one of the most critical goals in learning history, distinguishing it from other sciences. This skill is not a natural skill that already exists in students but is a skill that needs to be developed in students, especially in studying history. This study aims to develop an instrument for assessing chronological thinking skills with the Rasch model. The development model adopted the Gall Borg development model by adjusting to the research objectives and needs. The adaptation of the Borg Gall model resulted in four stages in this study: (1) needs analysis and preliminary investigation, (2) planning and preparation of product development, (3) expert validation, and (4) instrument implementation. This research was conducted in Senior High School (SMA), involving 120 students from three schools. Sampling was carried out employing the proportional sampling technique. The data was collected using validation sheets, tests, and assessment sheets (scoring rubric). Data analysis was then performed with the Quest Program utilizing the Partial Credit Model (PCM). The results showed that the chronological thinking skills assessment instrument with the Rasch model was valid and reliable. The validity value of items that fit the model ranged from 0.77 to 1.30, and the instrument reliability value of 0.76 was in the high category. Therefore, it could be concluded that the assessment instrument developed can measure students' chronological thinking skills.